Diabetes mellitus is associated with increased mortality and severity of disease in COVID-19 pneumonia – A systematic review, meta-analysis, and meta-regression. Issue 4 (July 2020) - Huang, Ian; Lim, Michael Anthonius; Pranata, Raymond
Abstract: Background and aims: Diabetes Mellitus (DM) is chronic conditions with devastating multi-systemic complication and may be associated with severe form of Coronavirus Disease 2019 (COVID-19). We conducted a systematic review and meta-analysis in order to investigate the association between DM and poor outcome in patients with COVID-19 pneumonia. Methods: Systematic literature search was performed from several electronic databases on subjects that assess DM and outcome in COVID-19 pneumonia. The outcome of interest was composite poor outcome, including mortality, severe COVID-19, acute respiratory distress syndrome (ARDS), need for intensive care unit (ICU) care, and disease progression. Results: There were a total of 6452 patients from 30 studies. Meta-analysis showed that DM was associated with composite poor outcome (RR 2.38 [1.88, 3.03], p < 0.001; I 2 : 62%) and its subgroup which comprised of mortality (RR 2.12 [1.44, 3.11], p < 0.001; I 2 : 72%), severe COVID-19 (RR 2.45 [1.79, 3.35], p < 0.001; I 2 : 45%), ARDS (RR 4.64 [1.86, 11.58], p = 0.001; I 2 : 9%), and disease progression (RR 3.31 [1.08, 10.14], p = 0.04; I 2 : 0%). Meta-regression showed that the association with composite poor outcome was influenced by age (p = 0.003) and hypertension (p < 0.001). Subgroup analysis showed that the association was weaker in studies with median age ≥55 years-old (RR 1.92) compared to <55 years-old (RR 3.48), and in prevalence of hypertension ≥25% (RR 1.93) compared to <25% (RR 3.06). Subgroup analysis on median age <55 years-old and prevalence of hypertension <25% showed strong association (RR 3.33) Conclusion: DM was associated with mortality, severe COVID-19, ARDS, and disease progression in patients with COVID-19. Highlights: Diabetes was associated with mortality, severity, and acute respiratory distress syndrome in Coronavirus Disease 2019. The association between diabetes and poor outcome was greater in studies with younger and less hypertensive patients. Gender, cardiovascular diseases, and pulmonary disease did not influence the association between diabetes and poor outcome.